Intravaginal progestagen for estrus and parturition control in sows - Gasperin, Bernardo Garziera; Freling, Gabriel Fernando; Ferreira, Rogério; de Oliveira, João Francisco Coelho; Bordignon, Vilceu; Gonçalves, Paulo Bayard Dias (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the use of intravaginal devices (IVD) for the control of reproductive events in swine. Sows at 112 days of pregnancy received an injection of PGF2α (control, n = 15) or PGF2α plus an IVD containing medroxyprogesterone acetate (IVD group, n = 14) for 48 hours. Sows initiated labor 27.7±1.6 and 82.3±3.8 h after PGF2α aplicaction, in control and treated groups, respectively. Regarding control of estrus cycle, ten sows received IVD for 12 days starting immediately after weaning, and estrus was confirmed 17.25±0.17 days after weaning, in comparison to 4.00±0.25 days for the control group. Intravaginal devices with progestagen can be applied for the control of reproduction in swine.